2016
DOI: 10.1177/1933719116632922
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Retrieval and Isolation From the Cervix for Noninvasive, First Trimester, Fetal Gender Determination in a Carrier of Congenital Adrenal Hyperplasia

Abstract: Congenital adrenal hyperplasia (CAH) is an autosomal recessive defect in cortisol biosynthesis that elevates fetal androgen levels to cause genital ambiguity and external genital masculinization in newborn females. Introducing dexamethasone in utero by 7 weeks gestation precludes virilization of affected females. However, identification of a male fetus prior to week 7 could avert the necessity of steroid treatment in half of pregnancies at risk of CAH. We recently introduced trophoblast retrieval and isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recently, HLA-G-positive extravillous trophoblasts have been retrieved from the endocervical canal and used for non-invasive prenatal testing (Bolnick et al 2016a , b ). These authors have shown that it is possible to collect extravillous trophoblasts from the cervix with a brush and separate trophoblasts from maternal cells for downstream analysis of fetal DNA, RNA, proteins and others (Drewlo and Armant 2017 ).…”
Section: Migratory Routes Of Extravillous Trophoblast In Normal Pregnmentioning
confidence: 99%
“…Recently, HLA-G-positive extravillous trophoblasts have been retrieved from the endocervical canal and used for non-invasive prenatal testing (Bolnick et al 2016a , b ). These authors have shown that it is possible to collect extravillous trophoblasts from the cervix with a brush and separate trophoblasts from maternal cells for downstream analysis of fetal DNA, RNA, proteins and others (Drewlo and Armant 2017 ).…”
Section: Migratory Routes Of Extravillous Trophoblast In Normal Pregnmentioning
confidence: 99%
“…TRIC has been used successfully with FISH and PCR to unequivocally determine fetal sex ( Bolnick et al , 2014 , 2016a ). DNA fingerprinting by targeted next-generation sequencing of STRs and SNPs has now been successfully conducted with EVT cells obtained by TRIC ( Jain et al , 2016 ).…”
Section: Utility Of Tric For Placental Researchmentioning
confidence: 99%
“…Most recently, trophoblast cells were identified via endocervical cells obtained via standard speculum exam with cytobrush and are being investigated as a possible additional option for noninvasive prenatal diagnosis. 25,26…”
Section: What New Tests Are Coming and What Are The Considerations Fomentioning
confidence: 99%